The Influence of Differentiated Instruction Towards Students Motivation in Learning English at Junior High school - Mutiara Patilima; Magvirah El Walidayni Kau; Haris Danial (Universitas Islam Negeri Palopo, 2026)
This study aims to examine the influence of Differentiated Instruction (DI) on students’ motivation in learning English at SMPN 10 Satu Atap Wonosari. This research employed a quantitative survey design involving 39 students from Grade 8 and Grade 9. Data were collected through Likert-scale questionnaires and analyzed using descriptive statistics and simple linear regression analysis. The findings revealed that the implementation of Differentiated Instruction was categorized as high across content, process, and product differentiation, with process differentiation emerging as the most dominant aspect, reflecting students’ positive responses toward adaptive instructional practices. Students’ motivation was also categorized as high, particularly in intrinsic motivation. Furthermore, the regression analysis indicated that Differentiated Instruction had a positive and significant influence on students’ motivation in learning English, t (37) = 3.47, p = .001. These findings suggest that Differentiated Instruction supports student-centered EFL learning by promoting students’ motivation through adaptive and varied instructional practices.